Prevalence of Burnout Among Health Workers in Iran: A Systematic Review and Meta-analysis. - Babakhanian, Masoudeh; kouhikheili, Maryam Qasemi; Mojarad, Fereshteh Araghian; Talebian, Fatemeh; Yaghoubi, Tahereh (Journal of Nursing & Midwifery Sciences, 2024)
Introduction: Burnout significantly impacts human service professions, reducing the sense of competence and successful performance of duties. This study aimed to investigate the prevalence of job burnout among healthcare workers in Iran. Methods: A systematic search was conducted according to the PRISMA checklist in databases such as PubMed, Scopus, Web of Science, PsycINFO, Magiran, Scientific Information Database (SID), and IranDoc from the inception of each database until December 30, 2023. Studies that used the Maslach burnout inventory to investigate the prevalence of burnout in health workers and had an observational design (including cross-sectional studies) were included. The selection of relevant studies was performed independently by two researchers at all stages of study selection, including screening, full-text review, and qualitative evaluation using the modified version of the HOY tool. Data implementation was done in Excel, and data analysis was conducted using STATA version 12. Results: A total of 63 articles were included. About 62.2% of the studies had a low risk of bias. A meta-analysis was performed using the random-effects method to calculate the prevalence of job burnout, and the average score of burnout was calculated as ES: [95% Conf interval = 0.38 (0.30 - 0.46)]. The degree of heterogeneity was reported as I2 = 99.66%, which is significant (P = 0.000), indicating high heterogeneity among the studies. Subgroup analysis was conducted to reduce heterogeneity. The results showed that the average burnout score increases with the sample size increase in the study, which is statistically significant (P < 0.001). Conclusions: To minimize burnout, it is suggested that supportive approaches, including access to psychosocial support, web-based services, psychological first aid, psychological support hotlines, and self-care techniques, be considered for healthcare workers during their service years.